2012
DOI: 10.1371/journal.pone.0032128
|View full text |Cite
|
Sign up to set email alerts
|

Activation of JNK Signaling Mediates Connective Tissue Growth Factor Expression and Scar Formation in Corneal Wound Healing

Abstract: Connective Tissue Growth Factor (CTGF) and Transforming growth factor-β1 (TGF-β1) are key growth factors in regulating corneal scarring. Although CTGF was induced by TGF-β1 and mediated many of fibroproliferative effects of TGF-β1, the signaling pathway for CTGF production in corneal scarring remains to be clarified. In the present study, we firstly investigated the effects of c-Jun N-terminal kinase (JNK) on CTGF expression induce by TGF-β1 in Telomerase-immortalized human cornea stroma fibroblasts (THSF). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 43 publications
3
36
1
Order By: Relevance
“…As previously described, VEGF and bFGF levels are closely correlated with neovascularization and fibroblast proliferation (5)(6)(7)(8). To further determine the association between MEBO and VEGF/bFGF, western blotting was used to determine the growth factor levels.…”
Section: Effects Of Mebo On the Protein Expression Of Vegf And Bfgfsupporting
confidence: 56%
See 1 more Smart Citation
“…As previously described, VEGF and bFGF levels are closely correlated with neovascularization and fibroblast proliferation (5)(6)(7)(8). To further determine the association between MEBO and VEGF/bFGF, western blotting was used to determine the growth factor levels.…”
Section: Effects Of Mebo On the Protein Expression Of Vegf And Bfgfsupporting
confidence: 56%
“…Increasing evidence has established the hypothesis that growth factors, including vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), are key regulators of normal and abnormal angiogenesis, and tissue repair in animals and humans (5)(6)(7)(8). VEGF promotes angiogenesis/vasculogenesis and vascular permeability, and enhances endothelial cell proliferation and migration as well as the adhesion of leukocytes (5,9).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of a-SMA is associated with scar formation in the cornea, 1,17 and we found that the expression of palladin in both the diseased cornea and the wounded cornea tended to overlap with that of a-SMA. Transforming growth factor-b 40 and its signaling pathways, 41 including those mediated by the MAPKs ERK, p38, and JNK, also play an important role in the formation of corneal stromal scars. Consistent with these previous observations, we have now found that TGF-b stimulated the expression of both palladin and a-SMA in HCFs in a manner dependent in part on p38, ERK, and JNK signaling, Comparison of collagen gel diameter for cells incubated as in (A) for 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with 3 lM PD98059 decreased CTGF-induced CXCL8/IL-8 protein secretion to only 5135 ± 435 qg/ml. CTGF activates diverse cellular signaling, and MAPK activation such as that of JNK and ERK has been reported previously [16,31,[36][37][38][39]. To elucidate more clearly whether MAPKs are involved in the signaling pathways mediating CTGF-induced CXCL8/IL-8 secretion, we measured the phosphorylated form of each kinase in CTGF-stimulated monocytes.…”
Section: Activation Of Jnk and P38 Mapk Is Required For Ctgf-induced mentioning
confidence: 97%